A Comparative Study Of The Algerian And Tunisian Last Year Secondary Education Syllabuses Of The English Language - Sonia Imerzoukéne (The Journal of Studies in Language, Culture and Society)
Generally, in undertaking a new educational reform, the first and most essential step is accorded to the design of new syllabuses. Both Algeria and Tunisia have designed new syllabi when reformed their educational systems to cope with the world‟s development and globalisation. The aim of this work is to analyse and compare the Algerian and Tunisian syllabuses of the last year secondary education. The aim of this comparison is to highlight the similarities and differences in the syllabuses to have an idea about how two historically and geographically related countries perceive and teach English as a foreign language. Both syllabuses are commonly designed in relation to the fact that learners study different streams. The two syllabuses are first analysed in terms of general goals and specific objectives, design procedures, syllabus type, language content (aspects and skills). Then, a comparison of each of these elements is made. The results indicate that both syllabuses are based on the same teaching approach- i.e. the Competency-Based Language Teaching, and pursue nearly the same goals and objectives. Both are communicative, task-based and cyclical. The two syllabuses draw a central importance to the teaching of the language skills as well as language aspects though the formulation and presentation of the contents is different.